Research paper on technology integration in higher education institutions: The DLSU-Manila College of Computer Studies experience - Molano, Renato Jose Ma. V. (Animo Repository, 2007)
The Management of Technology in Education is becoming an important and crucial trend in the 21st century academic pursuits. It is the goal of this paper to be able to show its relevance in every school's endeavor as well as to give a clear perspective of the what's, how's and why's of pursuing technology integration in all modem-day curriculum, whether this be among basic institutions. secondary schools. tertiary education or graduate programs. Although, this integrating paper will give focus on the College of Computer Studies (CCS) of De La Salle University -Manila (DLSU) where the proponent is associated with, any school for that matter can benefit from this paper. since the experiences and insights gained are universal in application. Even the paper being studied, "Managing Technology Efficiently in California K-12 Schools" involved only schools in one state of the U.S., yet the learning gained, and recommendations made by the authors are practical and easily understood and applicable. (Caspary et al, 2001). Technology Integration in Education is no easy task. As in any major project or endeavor. Planning is fundamental to its success. Technology Planning is not just a one-shot thing. Though it looks simple from a macro perspective, it involves more than just purchasing lnformation and Communications Technologies (lCTs), giving training to people concerned, then implementing it. The paper reveals a lot about its complexities, especially in the cost Educational Technology entails. There are several experiences in DLSU and CCS that corroborates the events that led to success in Technology integration among the schools studied in the said paper. Hopefully, this will guide DLSU and CCS to further enhance its strategies in ensuring 100% integration of technology in its educational system.